THE EVOLUTION OF MUNICIPAL WASTE GENERATION AT THE LEVEL OF IALOMITA COUNTY, ROMANIA - ELIZA GHEORGHE; RALUCA MITULESCU (AVRAM); NICOLETA ILIE (MARIN); ALECSANDRA PĂRNUȘ (RUSU) (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Municipal (for urban and rural) waste accounts about 7% to 10% of total waste generated in the Union. However, this waste stream is one of the most complex to manage, and the way it is operated is generally a good indication of the quality in a country’s overall waste management system. The challenges of municipal waste management are determined by the fact that it is very complex and mixed in composition, is in the close proximity to citizens, it has a very high degree of public visibility and has consequences for the environment and the health of the population. Therefore, municipal waste management requires a very complex system, including an efficient collection scheme, an efficient sorting system and proper tracking of waste streams, the active involvement of citizens and businesses, the adaptation of infrastructure to the specific composition of waste and a detailed financing system. Countries that have developed efficient municipal waste management systems generally perform better in terms of overall waste management, including the achievement of recycling targets. In 2018, the EU set ambitious new targets for recycling, packaging waste and landfills. The aim of these new rules is to promote the transition to a more sustainable model, known as the circular economy. In March 2020, the European Commission presented an Action Plan on the Circular Economy aimed at reducing waste through better resource management.